Urbanisme et prévention situationnelle : le cas de la dispute des professionnels à Lyon - Bilel Benbouzid (Métropoles)
In this article, the author examines a dispute on the establishment of a municipal advisory committee on situational crime prevention, an experimental device implemented in Lyon to integrate safety in urban area planning. The author analyzes the critical moment when people in charge of planning and those of safety had to compete and measure themselves around its acceptability and its definition. The challenge is to take seriously the logic of justification of people in order to analyze how they find an agreement. We observe that situational crime prevention appears like a great catalyst of the debate about the meaning of the city. In creating this experimental instrument, the City of Lyon has created, without having the intention, a space to debate on the objection against situational crime prevention. This latter appears as the means for people in charge of safety and planning to reclaim a number of political and moral issues by displaying the superiority of politics on technician competence.